Impaired memory B‐cell development and antibody maturation with a skewing toward IgE in patients with STAT3 hyper‐IgE syndrome. Issue 12 (16th August 2019) - van de Veen, Willem; Krätz, Carolin E.; McKenzie, Craig I.; Aui, Pei M.; Neumann, Jens; van Noesel, Carel J. M.; Wirz, Oliver F.; Hagl, Beate; Kröner, Carolin; Spielberger, Benedikt D.; Akdis, Cezmi A.; van Zelm, Menno C.; et al.
Abstract: Background: Signal transducer and activator of transcription 3 hyper‐IgE syndrome (STAT3‐HIES) is caused by heterozygous mutations in the STAT3 gene and is associated with eczema, elevated serum IgE, and recurrent infections resembling severe atopic dermatitis, while clinically relevant specific IgE is almost absent. Methods: To investigate the impact of STAT3 signaling on B‐cell responses, we assessed lymph node and bone marrow, blood B and plasma cell subsets, somatic hypermutations in Ig genes, and in vitro proliferation and antibody production in STAT3‐HIES patients and healthy controls. Results: Lymph nodes of STAT3‐HIES patients showed normal germinal center architecture and CD138 + plasma cells residing in the paracortex, which expressed IgE, IgG, and IgM but not IgA. IgE + plasma cells were abundantly present in STAT3‐HIES bone marrow. Proliferation of naive B cells upon stimulation with CD40L and IL‐4 was similar in patients and controls, while patient cells showed reduced responses to IL‐21. IgE, IgG1, IgG3 and IgA1 transcripts showed reduced somatic hypermutations. Peripheral blood IgE + memory B‐cell frequencies were increased in STAT3‐HIES, while other memory B‐cell frequencies except for IgG4 + cells were decreased. Conclusions: Despite impaired STAT3 signaling, STAT3‐HIES patients can mount in vivo T‐cell–dependent B‐cell responses, while circulating memory B cells, except for those expressing IgG4 and IgE, were reduced. Reduced molecular maturation demonstrated the critical need of STAT3 signaling for optimal affinity maturation and B‐cell differentiation, supporting the need for immunoglobulin substitution therapy and explaining the high IgE serum level in the majority with absent allergic symptoms. Abstract : STAT3‐HIES patients have reduced plasmablast and memory B‐cell frequencies, while showing normal IgE + B‐cell frequencies. Despite normal lymph node GC architecture, STAT3‐HIES B cells show reduced proliferation in response to IL‐21 and reduced IGHV SHM levels. Relatively large numbers of IgE + plasma cells were detected in STAT3‐HIES patients' bone marrow and lymph node tissue. Abbreviations: GC, Germinal Center; HIES, hyper IgE syndrome; IGHV, immunoglobulin heavy chain variable region gene; SHM, somatic hypermutation; STAT3, signal transducer and activator of transcription 3.